Social Work in Higher Education: Internships in Opportunity Programs. Issue 4 (8th August 2018) - Bessaha, Melissa L.; Solis, Carmen L.; Franks, Cheryl L.; Yoon, Heejin; Dualeh, Delmar; Monroy-Caceres, Hugo; Cuesta, Gabrielle; Rodriguez, Eric
ABSTRACT: Field education is essential to the development of professional social workers. Despite the significant overlap in social work's and higher education's missions and values, there is a scarcity of social work internships specifically in higher education settings. The placement of social work interns in institutions of higher education provides a setting where they can develop new knowledge and skills and increase their capacity to support college students toward academic success. This conceptual article discusses the role of social work in higher education and provides a model social work internship in an opportunity program, including its creation, development, challenges, outcomes, and future direction.